Implementasi Perlindungan terhadap Anak Silver Korban Eksploitasi Ekonomi di Kota Bandar Lampung Perspektif Fiqh Siyasah - Muhammad Alif Gibralthar; Relit Nur Edi; Rudi Santoso (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The phenomenon of “silver children” in Bandar Lampung City indicates that economic exploitation of children continues to occur, influenced by factors such as poverty, the social environment, and weak family supervision, thereby undermining children’s rights to education, health, and social development. This study aims to analyze the implementation of protection measures for “silver children” who are victims of economic exploitation in Bandar Lampung City and to examine them from the perspective of fiqh siyasah. This study employs an empirical legal method with a qualitative descriptive approach through interviews and literature review. The findings indicate that the local government has implemented protective measures through social assessment, rehabilitation, guidance, social assistance, family economic empowerment, and interagency coordination. However, this implementation has not been optimal due to constraints such as limited rehabilitation facilities, weak post-counseling supervision, family economic factors, and children returning to the streets. From a fiqh siyasah perspective, government policies have reflected the state’s responsibility toward child protection but have not fully realized the principles of public interest and the objectives of maqashid al-shariah. This study underscores the importance of strengthening social protection policies that are more comprehensive, sustainable, and family empowerment based in addressing children who are victims of economic exploitation